Controle de convencionalidade: crítica ao entendimento do Supremo Tribunal Federal - Santos, Vanessa de Campos Melo (2016)
This dissertation aims to analyze the jurisprudence of the Supreme Court in the light of conventionality control institute focused on the Inter-American Court of Human Rights and the interpretation that it does about the international human rights treaties. To emphasize the importance and necessity of dialogue among courts for the construction of ius commune of human rights. In order to do so, the work was divided into four parts. Initially, related to the Federal Constitution of Brazil in 1988 and the international human rights treaties. After that, run to an examination of conventionality control. Afterwards, discuss the Supreme Court jurisprudence. Finally, from the data collected, analyzed and compared critically pondered that the Supreme Court in this matter is far short of what is expected of the highest court of the Brazilian judiciary and guardian of the Brazilian Federal Constitution